Problem-Based Learning Could Tackle the Issue of Insufficient Education and Adherence in People Living With HIV/AIDS - Zhang, Yang; Xu, Guangyong; Hou, Jianhua; Shi, Peirong; Chang, Suhua; Wu, Amos; Song, Aixin; Gao, Meixia; Cheng, Xiangpu; Cui, Dan; Wu, Hao; Huang, Xiaojie; et al. (Frontiers in Pharmacology, 2019)
Background: Poor medication adherence is still the main cause of antiretroviral therapy (ART) failure among people living with HIV/AIDS (PLWHA). Effective behavioral interventions are needed to improve HIV awareness and medication adherence. Methods: In this retrospective cohort study, we assessed the effect of problem-based learning (PBL) approaches to HIV-related education and adherence outcomes among PLWHA and a college student sample. In our study, compared with 309 demographic-matched control participants using conventional counseling methods (109 PLWHA and 200 college students), 321 subjects (111 PLWHA and 210 college students) chose to learn HIV-related knowledge via PBL-integrated methods. Co-primary outcomes were self-administered questionnaire after HIV-related education by all participants and self-reported medication adherence by new diagnosed PLWHA, measured in terms of the number of missed doses in the past week at each of the seven visits during a 1-year period. Multi-regression models adjusting different co-variates were used to test the robustness of HIV awareness and adherence association. Mediation model was used to investigate the relationship between PBL training, awareness of HIV and ART adherence. Results: The knowledge scores of participants in the PBL group were higher than those in the controls (P = 0.001), especially the subgroup of new diagnosed PLWHA in the PBL group (P = 0.001). The HIV-related health scores of the PBL college students were also higher than those of subjects exposed to conventional education (P < 0.001). There was no significant difference between the two by new diagnosed PLWHA groups in the number of missed doses during the past week at each visit except at the first follow-up visit (P = 0.018). The indirect effect of PBL-integrated education on ART adherence at the 2-week-visit through HIV awareness, had a point estimate of 0.0349 and a 95% bias-corrected bootstrap confidence interval of 0.0061~0.0874 in new diagnosed PLWHA. Conclusions: PLWHA and college students using PBL showed improved awareness of HIV and higher levels of recent ART adherence; however, there was no change in long-term ART adherence in new PLWHA.